The Gene FvTST1 From Strawberry Modulates Endogenous Sugars Enhancing Plant Growth and Fruit Ripening - Rashid, Arif; Ruan, Haixiang; Wang, Yunsheng (Frontiers in Plant Science, 2022)
Sugar is an important carbon source and contributes significantly to the improvement of plant growth and fruit flavor quality. Sugar transport through the tonoplast is important for intracellular homeostasis and metabolic balance in plant cells. There are four tonoplast sugar transporters (FvTST1-4) in strawberry genome. The qRT-PCR results indicated that FvTST1 has a differential expression pattern in different tissues and developmental stages, and exhibited highest expression level in mature fruits. The yeast complementation assay showed that FvTST1 can mediate the uptake of different sugars, such as fructose, glucose, sucrose, and mannose. Subcellular localization analyses revealed that FvTST1 was mainly targeted to the tonoplast. Transient expression of FvTST1 in strawberry fruits enhanced both fruit ripening and sugar accumulation. Furthermore, FvTST1-transformed tomato plants exhibited higher sucrose and auxin content, enhanced seed germination and vegetative growth, higher photosynthetic rate, early flowering, and bore fruit; fructose and glucose levels were higher in transgenic fruits than those in the control. Transcriptomic analysis indicated that the auxin signaling pathway was highly enriched pathway in up-regulated Gene-ontology terms. In transgenic plants, genes encoding transcription factors, such as phytochrome-interacting factors PIF1, -3, and -4, as well as their potential target genes, were also induced. Collectively, the results show that FvTST1 enhances plant growth and fruit ripening by modulating endogenous sugars, and highlight the biological significance of this gene for future breeding purposes.